ISTILAH BUDAYA DALAM RITUAL ANTAR TUMPANG ADAT PERNIKAHAN PADA MASYARAKAT MELAYU DI NGABANG - Maharani, Suci; Salem, Lauriensius; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstractthe purpose of the study was to describe the lingual form of cultural terms in ritual Antar Tumpang Adat Pernikahan of malay people in Ngabang. describe the meaning of cultural terms in ritual Antar Tumpang Adat Pernikahan of malay people in Ngabang. describe cultural meaning ritual Antar Tumpang Adat Pernikahan of malay people in Ngabang.in the form of spells, myths, taboos, and oral literature.The method in this research is descriptive qualitative. The approach is sociolinguistics. Data collection techniques are competent listening techniques, see free involvement, and record. cultural terms in ritual Antar Tumpang Adat Pernikahan of malay people in Ngabang consists of 50 data.Data from this study are expected to be used as a reference for further research and can be used as cultural heritage objects that should be preserved and can be used as guidelines in communicating a day, especially the user community through local wisdom hidden in this custom.Keywords: cultural, Ritual Antar Tumpang, Adat Pernikahan of malay people,  Ngabang